Integrated surgical treatment: a new model for treating secondary extremity lymphedema based on algorithms - Chen, Junzhe; Chen, Zongcan; Wu, Xiangkui; Li, Hai; Xiao, Shune; Wei, Zairong; Zhang, Yixin; Deng, Chengliang (Frontiers in Oncology, 2026)
Secondary extremity lymphedema (SEL) is a chronic and progressive disorder resulting from impaired lymphatic drainage, most commonly following oncologic interventions such as breast or gynecological cancer surgery. Characterized by the accumulation of lymphatic fluid, progressive inflammation, adipose hypertrophy, and tissue fibrosis, SEL poses significant therapeutic challenges, particularly in its advanced stages. While conservative management remains the first-line treatment for mild cases, surgical intervention becomes essential in moderate to severe disease. Surgical approaches are generally categorized into physiological procedures, which aim to restore lymphatic continuity (e.g., lymphaticovenous anastomosis [LVA], vascularized lymph node transfer [VLNT]), and excisional techniques, which remove fibrotic and adipose tissue (e.g., liposuction, Charles procedure). Increasingly, integrated strategies combining physiological and excisional methods have demonstrated superior outcomes by targeting both fluid and solid components of the disease. However, multiple challenges remain, including the identification of functional lymphatic vessels, donor site morbidity, variability in long-term outcomes, and a lack of standardized surgical algorithms. Emerging evidence supports a component-based, individualized surgical framework tailored to disease severity, pathological tissue composition, and lymphatic functionality. Combined approaches such as the “3L” strategy (LVA, VLNT, and liposuction) have shown promise in enhancing volume reduction, minimizing infection risk, and improving quality of life. This review synthesizes recent advancements in SEL surgery and proposes a practical decision-making algorithm, the ISTL algorithm, which integrates clinical evaluations, imaging diagnostics, and surgical interventions for personalized treatment planning and improved long-term surgical outcomes.Clinical Trial RegistrationThis study was registered at the China Clinical Trial Registration (www.chictr.org.cn) with the registration number NCT06920732.